2009
DOI: 10.1021/jm9012328
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Pipemidic Acid Autotaxin Inhibitor

Abstract: Autotaxin (ATX, NPP2) has recently been shown to be the lysophospholipase D responsible for synthesis of the bioactive lipid lysophosphatidic acid (LPA). LPA has a well-established role in cancer, and the production of LPA is consistent with the cancer-promoting actions of ATX. Increased ATX and LPA receptor expression have been found in numerous cancer cell types. The current study has combined ligand-based computational approaches (binary quantitative structure-activity relationship), medicinal chemistry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…The differences in substrate-specific inhibition by the two groups of compounds led us to hypothesize that they might interact with different surfaces of ATX, as has been suggested for other ATX inhibitors showing substrateselective effects (Hoeglund et al, 2010). Computational docking studies were performed using one of the recently solved crystal structures of ATX (2XR9) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in substrate-specific inhibition by the two groups of compounds led us to hypothesize that they might interact with different surfaces of ATX, as has been suggested for other ATX inhibitors showing substrateselective effects (Hoeglund et al, 2010). Computational docking studies were performed using one of the recently solved crystal structures of ATX (2XR9) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of ATXmediated hydrolysis of various chain-length LPC substrates was determined via Amplex Red choline release assay as described previously (Hoeglund et al, 2010;North et al, 2010). Briefly, 60-ml triplicate reaction volumes were loaded into 96-well, half-area plates (Corning Inc., Corning, NY) in assay buffer consisting of 50 mM Tris, 5 mM CaCl 2 , and 30 mM fatty acid-free BSA (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study resulted in the identification of 18 novel CPEs, four of which showed minimal or no toxic effects (Golla et al, 2012). Hoeglund et al (2010) used QSAR modeling combined with synthetic optimization in a follow up to their most potent hit from a 2008 in silico screen for inhibitors of autotaxin. Autotaxin is an autocrine motility factor and has been linked to cancer progression, multiple sclerosis, obesity, diabetes, Alzheimer's disease, and chronic pain through the production of lysophosphatidic acid (LPA) (Kawagoe et al, 1997;Euer et al, 2002;Baumforth et al, 2005;Boucher et al, 2005;Umemura et al, 2006;Inoue et al, 2008).…”
Section: Quantitative Structure-activity Relationship Modelsmentioning
confidence: 99%
“…Recent studies have shown that targeting either the LPA3 receptor or ATX effectively reduces melanoma cell viability (Altman et al 2010). Furthermore, research devoted to producing inhibitors and antagonists targeting the ATX-LPA receptor axis has yielded a large variety of compounds (Albers, Dong et al 2010;Altman et al 2010;Baker, Fujiwara et al 2006;Block, Duff et al 2010;Hoeglund, Bostic et al 2010;North, Howard et al 2010;Xu, Yang et al 2009), suggesting the critical role of this pathway in cancer. Herein we tested the in vitro capability of another antagonist of the LPA3 receptor and the lysophospholipase D activity of autotaxin, BrP-LPA, among the MeWo melanoma cell line.…”
mentioning
confidence: 99%